1967
DOI: 10.1115/1.3617021
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on an Ultrastable Gas Journal Bearing

Abstract: Approved Prepared underC o n t r a c t N o n r -3 7 3 0 ( 0 0 ) Task NR 061-131 t h e o r e t i c a l l y t h a t t h i s p o s s i b i l i t y i s p a r t i c u l a r l y advantageous f o runloaded j o u r n a l b e a r i n g s . This paper d e s c r i b e s c o r r o b o r a t i n g experiments. The experiments i n c l u d e d t h erunning of an unloaded b e a r i n g up t o speeds of 60,000 rpm and t h e c o l l e c t i o n of s t e a d y s t a t e load-displacement a t t i t u d e a n g l e d a t a a t i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Grooved bearings have proven to be the most promising solution in terms of stability among selfacting gas bearings [59]. Malanoski experimentally showed that the herringbone-grooved journal bearings (HGJB) were less likely to suffer from the whirl instability than other types of dynamic journal bearings [60]. • Compliant-Surface GBs.…”
Section: Figure 3 An Overview Of Typical Gb Types Categorized By Rigimentioning
confidence: 99%
See 4 more Smart Citations
“…Grooved bearings have proven to be the most promising solution in terms of stability among selfacting gas bearings [59]. Malanoski experimentally showed that the herringbone-grooved journal bearings (HGJB) were less likely to suffer from the whirl instability than other types of dynamic journal bearings [60]. • Compliant-Surface GBs.…”
Section: Figure 3 An Overview Of Typical Gb Types Categorized By Rigimentioning
confidence: 99%
“…The NGT was experimentally validated first in its incompressible form by Hirs [97], who ran a floating HGJB with a load applied on the non-rotating bushing. Malanoski [60] ran a 38 mm shaft supported by shallow-grooved HGJBs without external load up to 60 kRPM with no sign of halfwhirl instability. Measurements of radial stiffness were in good agreement with the 1D centered NGT, with most of the measurement points within 10% deviation from the concentric NGT predictions.…”
Section: The Experimental Validation Of the Classical Ngtmentioning
confidence: 99%
See 3 more Smart Citations